[OP.7C.04] GENETIC ASSOCIATION STUDY IDENTIFIES COMMON VARIATION IN PHACTR1 TO ASSOCIATE WITH FIBROMUSCULAR DYSPLASIA. (September 2016) - Kiando, S.; Tucker, N.; Castro-vega, L.; Cusi, D.; Galan, P.; J.-P., Empana; Olin, J.; Gornik, H.; Plouin, P.-F.; Kullo, I.; Milan, D.; Ganesh, S.; et al.
Abstract : Objective: Fibromuscular dysplasia (FMD) is a nonatherosclerotic vascular disease leading to stenosis, dissection and aneurysm affecting mainly the renal and cerebrovascular arteries. FMD has higher prevalence in females (80–90%) and predisposes to hypertension and stroke but its pathophysiology is unclear. Design and method: We performed a multistage genetic association study (1, 154 patients and 3, 895 controls) from five case-control cohorts. We investigated the association between rs9349379 in the phosphatase and actin regulator 1 gene (PHACTR1) and carotid traits by echo-tracking in healthy volunteers, the expression of PHACTR1 by genotypes in human fibroblasts, protein staining pattern in human carotids, and vasculature development after Phactr1 knockdown in zebrafish. Results: We show significant and replicated association of rs9349379, a common variant (effect allele frequency 0.60) in PHACTR1 with FMD (OR = 1.39, P = 7.4 × 10–10). rs9349379 associates with greater intima media thickness (P = 3.9 × 10-5) and wall to lumen ratio (P = 0.001), previously reported to be increased in FMD patients. Immunohistochemistry detected PHACTR1 in endothelium and smooth muscle cells of FMD and normal carotid arteries. We also found higher expression of PHACTR1 in FMD risk allele carriers (N = 86, P = 0.003). Phactr1 knockdown in zebrafish resulted in dilated vessels indicating impaired vascular development. Conclusions: We report the first susceptibility locus for FMD in the largest genetic association study conducted so far. Our data reveal a common genetic variant in PHACTR1, previously reported to associate with coronary artery disease, migraine, and cervical artery dissection supporting a complex genetic pattern of inheritance and indices of shared pathophysiology between FMD and other cardiovascular and neuromuscular diseases.